Central diabetes insipidus in pediatric patients with Langerhans cell histiocytosis: Results from the JLSG‐96/02 studies. Issue 1 (11th September 2018) - Sakamoto, Kenichi; Morimoto, Akira; Shioda, Yoko; Imamura, Toshihiko; Imashuku, Shinsaku; ,
Abstract: Purpose: We analyzed central diabetes insipidus (CDI) development in pediatric patients with Langerhans cell histiocytosis (LCH) treated according to the Japan LCH Study Group (JLSG) regimen, which is the combination chemotherapy including cytarabine (Ara‐C). Methods: Retrospective data from 317 patients (multisystem disease (MS), n = 206; multiple focal bone (MFB), n = 111) treated according to the JLSG‐96/02 regimens were analyzed. Results: The median follow‐up duration was 10.6 years (range, 0.1–21.1). A total of 50/317 (15.8%) patients developed CDI (MFB, n = 4; MS, n = 46). Of the 50 cases, CDI was already present at the time of LCH diagnosis (pre‐CDI) in 25, and it newly developed after the diagnosis and initiation of treatment (post‐CDI) in the other 25 cases. The cumulative incidence of post‐CDI at 10‐year calculated by Kaplan–Meier analysis was 9.0% for total and 12.0% for MS patients. A positive correlation with LCH lesions at the CNS risk sites at diagnosis was found in pre‐CDI cases (17/164 vs 8/171; P = 0.0359), but not in post‐CDI cases (14/129 vs 11/163; P = 0.254). Multivariate analysis showed that relapse at the CNS risk sites was significantly associated with post‐CDI development (hazard ratio: 4.70; 95% CI, 1.29–17.1, P < 0.05). Conclusions: In the JLSG‐96/02 studies, CDI developed in 15.8% of the cohort in which half as pre‐ and the other half as post‐CDI. Relapse, particularly at the CNS risk sites, was linked with the development of post‐CDI.